Keberkesanan Waktu Pembelajaran untuk Pengajaran Matematik kepada Pelajar PAUD - Devy Nurdiana; Syahira Luqna Aqila M; Fatkhur Syahrul Ramadhan (Advances in Humanities and Contemporary Studies, 2022)
Activities or teaching and learning activities that we can make appropriate if we minimize and observe the wasted time missed and accuracy in delivering material. This is very useful for learning because if the efficiency of learning is successful it will save time, achieving learning goals. And the allocation of learning time, especially for mathematics for Students in early childhood education (early childhood education) will have a good impact on the further development of teaching and learning efficiency hours referring to the curriculum applicable in schools, l Learning mathematics and language for early childhood education students in schools, and for the duration of study time in Early Childhood Education schools, has also been regulated in early childhood education curriculum regulations issued by the government. However, there must be effective in achieving teaching and learning outcomes. Well-organized learning activities will ensure that half of the activities are carried out successfully. For children, for educators, the implementation of early childhood learning activities becomes a challenge in itself, especially in determining teaching and learning schedules that are truly in accordance with the needs of children.